KORUPSI DAN DEMOKRASI - Mathias Daven (Jurnal Ledalero, 2016)
Democracy is often seen as a political system which is capable of lessening or preventing corruption. Countries with a democratic system are regarded as relatively free of corrupt practices. Meanwhile, authoritarian political systems are seen as riddled through with corrupt practices because they are not capable of protecting political officials from such practices. However it is apparent that corruption scandals are frequently encountered in democratic systems. Various corruption scandals that befall politicians in Western Europe, the USA and Japan indicate the reality that democratic procedures are not, on their own, capable of protecting officials from corruption. What calls for debate among academics is: Which aspect of democracy can prevent, and which aspect can permit corrupt practices? How can the relationship between corruption and democracy be explained? This essay is presented as a small contribution to this debate.